2023
DOI: 10.3390/genes14030691
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Telomerase and Telomere-Associated Proteins in B-Acute Lymphoblastic Leukemia

Abstract: Telomeres and telomerase are closely linked to uncontrolled cellular proliferation, immortalization and carcinogenesis. Telomerase has been largely studied in the context of cancer, including leukemias. Deregulation of human telomerase gene hTERT is a well-established step in leukemia development. B-acute lymphoblastic leukemia (B-ALL) recovery rates exceed 90% in children; however, the relapse rate is around 20% among treated patients, and 10% of these are still incurable. This review highlights the biologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 214 publications
(181 reference statements)
0
4
0
Order By: Relevance
“…However, some studies have also found that telomere elongation was linked to poor prognosis in ALL [ 22 ]. Evidently, there was no consistent pattern in the function of telomeres and telomerase in ALL, especially considering the various potential atypical roles of TERT [ 23 ]. Our analysis revealed that genetically predicted longer TL increases the risk of ALL and suggests that longer TL is the primary driver of ALL onset; measuring the difference in TL length between tumor cells before the onset of ALL (before the malignant clone proliferates extensively) and healthy individuals may potentially predict the onset of ALL in advance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have also found that telomere elongation was linked to poor prognosis in ALL [ 22 ]. Evidently, there was no consistent pattern in the function of telomeres and telomerase in ALL, especially considering the various potential atypical roles of TERT [ 23 ]. Our analysis revealed that genetically predicted longer TL increases the risk of ALL and suggests that longer TL is the primary driver of ALL onset; measuring the difference in TL length between tumor cells before the onset of ALL (before the malignant clone proliferates extensively) and healthy individuals may potentially predict the onset of ALL in advance.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis revealed that genetically predicted longer TL increases the risk of ALL and suggests that longer TL is the primary driver of ALL onset; measuring the difference in TL length between tumor cells before the onset of ALL (before the malignant clone proliferates extensively) and healthy individuals may potentially predict the onset of ALL in advance. In terms of treatment, telomerase inhibitors (such as imetelstat) may enhance standard ALL therapy [ 23 ]; therefore, the prospect of combined targeted therapy against telomeres and telomerase in treating ALL is promising.…”
Section: Discussionmentioning
confidence: 99%
“…Among these subtypes, ALL mainly affects children and stems from the uncontrolled proliferation of bone marrow hematopoietic precursor cells. While advancements in therapeutics have improved overall survival rates, factors like lineage switching and the emergence of mixed lineages during relapses or chemotherapy often alter the prognosis of the disease [2].…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase, in particular, has been extensively studied in various cancer types, including leukemias, due to its involvement in carcinogenesis. The dysregulation of the human telomerase gene is a well-documented event in the development of leukemia [2]. The role of MLL gene translocations in the pathogenesis of acute leukemia is significant, often leading to a bleak prognosis.…”
Section: Introductionmentioning
confidence: 99%